Employability of Bachelor of Science (Agriculture) Graduates of Bangabandhu Sheikh Mujibur Rahman Agricultural University - Afrad, Md Safiul Islam; Barau, & Aliyu Akilu (Journal of Technical Education and Training, 2019)
Employability is a contemporary global concern of developing countries which indirectly affects other categories of countries. Hence, the necessity for institutions turning out graduates to focus on ensuring their products meet market demands. The present study was therefore, centred on employability of Bachelor of Science Agriculture graduates of BSMRAU. Mixed research methods were adopted to conduct a survey on 140 (Master of Science students, Alumni and Service providers) respondents concerning generic skills and job performance. Quantitative data were analysed using descriptive statistics such as mean, percent, frequency and range in SPSS software, while qualitative data was analysed through collection of themes with respect to the study objectives. Results revealed that majority of graduates dominantly acquired generic skills related to communication and ICT, interpersonal, teamwork and leadership skills, and self-management and personal development skills from Agricultural Extension and Rural Development offered courses. The employability trend of Bachelor of Science Agriculture graduates was obtained to be high in the early years after graduation and decreases afterwards. Governmental organisations that include research, extension, education and bank absorbed majority of the graduates. Higher level of satisfaction was expressed in teaching-learning, communications skills and process control, while curriculum update and knowledge achievement were low satisfied. Major perceived strength was adherence to academic calendar while less extracurricular activities was the major weakness. Carrying out practical in a practical way and provision of some important laboratory equipment were the key areas suggested for improvement.